The impact of maternal adiposity specialization on infant birthweight: upper versus lower body fat. (November 2016) - Sundermann, Alexandra C.; Abell, Troy D.; Baker, Lisa C.; Mengel, Mark B.; Reilly, Kathryn E.; Bonow, Michael A.; Hoy, Gregory E.; Clover, Richard D.
Abstract: Background: The specialization of human fat deposits is an inquiry of special importance in the study of fetal growth. It has been theorized that maternal lower-body fat is designated specifically for lactation and not for the growth of the fetus. Objective: Our goal was to compare the contributions of maternal upper-body versus lower-body adiposity to infant birth weight. We hypothesized that upper-body adiposity would be strongly associated with infant birth weight and that lower-body adiposity would be weakly or negligibly associated with infant birth weight—after adjusting for known determinants. Study design: In this prospective cohort study, 355 women initiated medical pre-natal care during the first trimester of pregnancy at The University of Oklahoma Health Sciences Center during 1990–1993. Maternal anthropometric measurements were assessed at the first clinic visit: (a) height; (b) weight; (c) circumferences of the upper arm, forearm, and thigh; and, (d) skin-fold measurements of the bicep, subscapular region, and thigh. Results: Infant birth weight was regressed on known major determinants to create the foundational model. Maternal anthropometric variables subsequently were added one at a time into this multiple regression model. The highest contribution by a single anthropometric variable to infant birthweight was, in order: subscapular skin-fold, forearm circumference, and thigh circumference. With one upper-body (subscapular skin-fold) and one lower-body (circumference of the thigh) adiposity measure in the model, the z-score regression coefficient (s.e.) was 85.7 g (30.8) [p = 0.0057] for maternal subscapular skin-fold and 19.0 g (31.6) [p = 0.5477] for circumference of the thigh. When the second-best upper-body contributor to infant birthweight (circumference of the forearm) was entered with one lower-body measure into the model, the z-score regression coefficient (s.e.) was 77.5 g (38.5) [p = 0.0451] for maternal forearm circumference and 14.1 g (38.5) [p = 0.7146] for circumference of the thigh. When both subscapular skinfold and forearm circumference were added to the model in place of BMI, the explained variance (r 2  = 0.5478) was similar to the model using BMI (r 2  = 0.5487). Conclusion: Upper-body adiposity – whether operationalized by subscapular skin-fold or circumference of the forearm – was a markedly larger determinant of infant birth weight than lower-body adiposity.